Innovation or Stagnation – Social Work Organisations as Models of Behaviour for Clients - Sher, Mannie (Socialinė teorija, empirija, politika ir praktika, 2014)
Tavistock Institute of Human Relations1 T: (+44) 020 7417 0407 F: (+44) 020 7417 0566 E: m.sher@tavinstitute.org W:www.tavinstitute.org W: www.grouprelations.com Presented at the conference: Reconstructing social work strategies in relation to authority and power University of Vilnius 8th November 2013 Summary The profession of social work is fundamentally concerned about the persisting problems of socially alienated people and communities. Social work, by relying on its long heritage of practical experience, intelligent conceptual models and leading edge methodologies for change, works consistently to develop radically different approaches to helping clients. They do so by challenging the government, welfare agencies and charities to review their strategies and practices across society as a whole. The profession of social work also has to manage the tension between a prevailing view of welfare services as a burden on the public purse and one which views welfare services as being for the good of society as a whole. Social policies and good social work services are a wise form of endowment in the potential of individuals and communities whose considerable resources and strengths for their and society’s mutual benefit are otherwise wasted. Key words: welfare; social work; sustainability; alienation; autonomy and independence; power and authority.